Absence of myotonic dystrophy in southern African Negroids is associated with a significantly lower number of CTG trinucleotide repeats. Issue 1 (January 1994) - Goldman, A; Ramsay, M; Jenkins, T
Abstract : Myotonic dystrophy (DM) is associated with an increased number of CTG repeats in the 3' untranslated region of the myotonin gene. Because DM has not been observed in southern African Negroids, a study of the CTG repeat polymorphism in this population was undertake. A total of 210 unrelated subjects was studied by PCR analysis of the trinucleotide repeat in the DM gene and the size and distribution of the CTG repeat were determined. The alleles ranged in length from five to 22 repeats. A previously undescribed BglI polymorphism was found which could lead to erroneous diagnosis of DM in people from this population. South African Negroids were found to have significantly fewer large repeat lengths than do white and Japanese populations. It is suggested that the occurrence of fewer large CTG repeats in the normal range may, in part, explain the absence of DM in southern African Negroids.